2009
DOI: 10.1037/a0016248
|View full text |Cite
|
Sign up to set email alerts
|

Validation of French-Canadian versions of the Empathy Quotient and Autism Spectrum Quotient.

Abstract: The primary objective of this study was to validate French-Canadian versions of the Autism Spectrum Quotient (AQ-F) and the Empathy Quotient (EQ-F) in normal and pathological samples. These versions of the scales were administered to 100 undergraduate university students in the hard science or humanities fields and to 23 individuals diagnosed with autism spectrum disorder (ASD). For both scales, obtained data were partially consistent with English versions. The EQ-F and AQ-F scores were negatively correlated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 11 publications
0
43
1
1
Order By: Relevance
“…Findings have also shown the AQ has no bias towards any particular age group [3, 6, 12]. These norms have been replicated in several UK samples [5, 10, 13], a Dutch sample [8], a Scottish sample [11], a French-Canadian sample [14] a US sample [15], and several nonwestern samples [9, 16, 17]. …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Findings have also shown the AQ has no bias towards any particular age group [3, 6, 12]. These norms have been replicated in several UK samples [5, 10, 13], a Dutch sample [8], a Scottish sample [11], a French-Canadian sample [14] a US sample [15], and several nonwestern samples [9, 16, 17]. …”
Section: Introductionmentioning
confidence: 84%
“…The original cutoff of 32 [5] has been suggested to correctly identify individuals with autistic traits; this has been supported by Baron-Cohen et al's [6] findings in the adolescent version of the AQ. Albeit, this threshold value has been challenged by [7, 10, 14, 20] who reported acceptable cutoff scores of 30, 30, 26, and 22, respectively. The present study found that cutoffs of 29 showed both high sensitivity and high specificity, and resulted in the correct classification of the greatest percentage of participants.…”
Section: Discussionmentioning
confidence: 99%
“…The original scale consists of 60 items (40 of them measure empathy and 20 filler items serve to distract the participants from focusing on empathy), but Lawrence et al (2004) suggested shortening the scale to 28 items loading on three factors: Cognitive Empathy (CE; 11 items), Emotional Reactivity (ER; 11 items) and Social Skills (SS; 6 items). This three-factor structure of the EQ has been partly confirmed in translated versions of the EQ in Japan (Wakabayashi et al, 2007), France (Berthoz et al, 2008), Canada (Lepage et al, 2009), Korea (Kim & Lee, 2010), Italy (Preti et al, 2011), Serbia (Dimitrijević et al, 2012) and Netherlands (Groen et al, 2015) and the scale has proven to be a valid and reliable tool for assessing empathy in both clinical and non-clinical samples.…”
Section: Introductionmentioning
confidence: 94%
“…The AQ has been revised for adolescents (Baron-Cohen et al 2006) and for Japanese, Dutch, and French speaking populations (Ketelaars et al 2008; Lepage et al 2009; Wakabayashi et al 2004). It has been employed in a number of recent studies of both clinical and general population samples to examine the relationships between ASD symptoms and a wide range of variables, including personality characteristics, self-referential cognition, and empathy (Austin 2005; Lombardo et al 2007; Wakabayashi et al 2006).…”
Section: Introductionmentioning
confidence: 99%